Comparative effectiveness of budesonide inhalation suspension and montelukast in children with mild asthma in Korea. (1st December 2020) - Shin, Jina; Oh, Seung-Jun; Petigara, Tanaz; Tunceli, Kaan; Urdaneta, Eduardo; Navaratnam, Prakash; Friedman, Howard S.; Park, Sung Woo; Hong, Song Hee
Abstract: Objective: The comparative effectiveness of low-dose budesonide inhalation suspension (BIS) versus oral montelukast (MON) in managing asthma control among children with mild asthma was assessed in Korea. Methods: Claims from Korea's national health insurance database for children (2–17 years) with mild asthma (GINA 1 or 2) who initiated BIS or MON during 2015 were retrospectively analyzed. Pre- and post-index windows were 1 year each. Adherence, persistency, asthma control, asthma-related health-care resource utilization, and costs were evaluated using unadjusted descriptive statistics and propensity score-matched regression analyses. Results: The number of children identified was 26, 052 for unmatched ( n  = 1, 221 BIS; n  = 24, 831 MON) and 2, 290 for matched populations ( n  = 1, 145 per cohort). Medication adherence, measured by proportion of days covered, was low for both cohorts but significantly higher for MON versus BIS (13.8% vs. 4.5%; p  < .001). Time to loss of persistency was longer for MON versus BIS (82.3 vs. 78.4 days, respectively; p  < .001). Mean number of post-index asthma-related office visits was 6.6 for BIS versus 8.3 for MON ( p  < .001). However, a greater proportion of patients in the BIS cohort had an asthma exacerbation-related office visit than the MON cohort (78.3% vs. 56.1%; p  < .001). Asthma-related total health-care costs were higher with MON versus BIS (₩ 190, 185 vs. ₩ 167, 432, respectively; p  < .001), likely driven by higher pharmaceutical costs associated with MON (₩ 69, 113 vs. ₩ 49, 225; p  < .001). Conclusions: Montelukast patients had better adherence, a longer time to loss of persistency, and were less likely to experience an exacerbation-related office visit in the post-index period than BIS patients.